Study of Blast Furnace Stave Cooler Based on Heat Transfer Analysis - Azad, Prashant Kumar; Singh, Mahendra (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
The life of blast furnace is increase due to technology of furnace cooling very important method for metallurgical industry. Blast furnace mathematical model of stave cooler has been developed for heat transfer analysis and compare to experimental. Using ANSYS® software calculating the heat transfer and temperature of stave cooler. The result calculating using software ANSYS® and compare with blast furnace placed in RSP with experimental model. Heat transfer stave cooling of blast furnace has been done at different temperature from 575k to 1675k the result is compare with experimental for better result, in the stave cooling of blast furnace nitrogen and nano fluid (Al2O3) also as a cooling fluid in the place of water.